Analisis kebolehgunaan laman sesawang Perpustakaan Universiti sebagai portal maklumat sehenti - Junaini, Syahrul Nizam (Persatuan Pustakawan Malaysia, 2014)
Web sites are a one-stop information portal for visitors who wish to access digital resources from public university libraries in Malaysia. Unfortunately, findings have indicated that there are university libraries whose web sites’ usability rate is still low making it difficult for users to access them. This paper examines the cause of the problem. A simple analysis was conducted to comapre the usability of a number of university library web sites focusing only on their main web site. Recommendations for improvements are made with the aim of making university library web sites a one-stop information portal of choice by the users.